Ferroptosis: a novel pharmacological mechanism against multiple myeloma - Shi, Jingbo; Lu, Yitong; Wei, Wenjian; Ma, Guodong; Li, Changnian; Li, Lulu; Wang, Yaru; Wang, Yan; Xu, Ruirong; Cui, Siyuan (Frontiers in Pharmacology, 2025)
BackgroundMultiple myeloma (MM) is a malignant disease characterized by the clonal proliferation of plasma cells in the bone marrow. Currently incurable, relapse and drug resistance remain significant challenges, necessitating the exploration of novel anti-MM agents. Ferroptosis, a form of cell death driven by iron-dependent lipid peroxidation, has emerged as a critical player in MM pathology and treatment. With advancing research, emerging evidence links ferroptosis to MM pathogenesis and therapeutic strategies. Natural products (NPs) and certain antitumor agents, owing to their broad bioactivities, demonstrate unique pharmacological advantages in MM therapy by targeting ferroptosis-related pathways.PurposeThis review systematically examines ferroptosis-related pathways in MM pathogenesis, focusing on pharmacological and toxicological mechanisms of natural products (NPs) and antitumor compounds in modulating ferroptosis-related pathways. It aims to provide novel insights and strategies for MM research and clinical therapy.MethodsWe systematically retrieved data from PubMed, Web of Science, ScienceDirect, SciFinder, Scopus, and the China National Knowledge Infrastructure (CNKI) spanning database inception to March 2025, followed by taxonomic integrative analysis of NPs’ and antitumor compounds’ echanistic classifications.ResultsNPs and antitumor compounds exert anti-MM effects via ferroptosis modulation, mechanistically mediated through: 1) lipid metabolism reprogramming; 2) ferritinophagy-driven iron homeostasis regulation; 3) Reactive oxygen species (ROS)-mediated oxidative stress potentiation; 4) autophagic activation; 5) Genes and proteins regulation.ConclusionNPs and antitumor compounds demonstrate therapeutic potential against MM through multi-dimensional ferroptosis modulation, yet clinical translation faces two critical hurdles: 1) predominant focus on single-target mechanisms lacking systems pharmacology-level network analysis; 2) overreliance on in vitro models with insufficient clinical validation. Prioritize developing biomarkers and ferroptosis inducers to advance novel ferroptosis-targeting anticancer compounds.